Benefits of β-glucans in patients with breast cancer: systematic literature review - Ferraz de Oliveira, Carolina Trabasso; Seto de Oliveira, Giovanna; Fernandes Junior, Hezio Jadir Fernandes Junior; Tallo, Fernando Sabia; Caricati-Neto, Afonso; Tantray, Junaid; Viana, Bianca Lorayne de Almeida; Rodrigues, Francisco Sandro Menezes (Journal of Medical Residency Review, 2024)
Breast cancer is the most prevalent cancer, totaling 50 thousand new cases per year, as well as being responsible for a high annual mortality rate. Some preventive measures are simple and easy to carry out, such as practicing physical activities, eating a healthy diet, not smoking, avoiding drinking alcohol, carrying out self-examinations and mammograms frequently. Several recent studies have demonstrated that the consumption of nutraceuticals rich in beta-glucans (β-glucans) can have a positive impact on both the prevention and treatment of breast cancer. β-glucans are natural polysaccharides found in the cell walls of fungi and yeast that promote the stimulation of cells that make up the immune system and modulation of tumor cells.